Central Auditory Processing Syndrome (SPAC) new perspectives towards symptom assessment - Díaz Rosell, Montserrat (2019)
The study of children and adults who have a hearing and auditory deficit that are not justified by a deficient auditory profile in the audiogram, has aroused the interest of numerous research groups in the last decades, whose result has been the definition and compilation of evidences towards the evaluation of Central Auditory Processing Disorder (CAPD). In this article we will make a historical journey through the definition of the syndrome and the different instruments used today for its diagnosis.